A left ventricular true aneurysm. Issue 6 (6th April 2018) - Saleh, Yehia; Almaghraby, Abdallah; Abdelkarim, Ola; Abdelnaby, Mahmoud; Hammad, Basma
Key Clinical Message: True ventricular aneurysm is a scarred wall that most commonly results after an unrevascularized ST elevation myocardial infarction. Patients usually present with heart failure, angina, ventricular arrhythmia, systemic embolization, or ventricular rupture. Diagnosis can be achieved via echocardiography, left ventricle angiogram, cardiac computed tomography, or cardiac magnetic resonance. Abstract : True ventricular aneurysm is a scarred wall that most commonly results after an unrevascularized ST elevation myocardial infarction. Patients usually present with heart failure, angina, ventricular arrhythmia, systemic embolization, or ventricular rupture. Diagnosis can be achieved via echocardiography, left ventricle angiogram, cardiac computed tomography, or cardiac magnetic resonance.